Linguistic and Cultural Component in Pandemic Coronavirus Discourse (German Humorous Texts and Metaphors) - N. A. Trofimova; Ya. A. Manukyan (Дискурс)
Introduction. This article is devoted to the linguocultural study of humorous texts/metaphors which appeared in German during the COVID-19 pandemic. The scientific novelty of the study lies in the previously unexplored study of the linguocultural specificity of German-language humour in the context of the coronavirus pandemic. The relevance of the research is due to the interest of modern linguistics in the study of national specificity of humour.Methodology and sources. The research is conducted within the framework of the linguocultural approach using descriptive, comparative and interpretative analysis methods. The illustrative material is described and interpreted as a product of an individual's speech self-expression, marking and evaluating himself and what is happening within the boundaries of his (ethno)culture.Results and discussion. The main thematic dominant theme in the COVID-19 pandemic discourse is “us and them in the context of the new reality”. The study showed: the pandemic discourse is characterised by expressiveness and axiology, irony and self-irony, stereotyping and interpretation of self and self through the prism of others. Pandemic / self-isolation → stress → carnivalisation of consciousness represent the average German as a person who overcomes reality and evaluates it on the basis of ethno-cultural ideas about norms and patterns of behaviour in certain circumstances (the concept Ordnung). Some contexts illustrate an ironic reinterpretation of the concept of Sicherheit.Conclusion. The representation of reality is constructed on the basis of mentality and national stereotypes; within German culture, the contexts reveal a cultural distinction and, on the level of ethno-cultural comparison, a contradiction of cultural codes.